1999
DOI: 10.1136/jnnp.67.4.532
|View full text |Cite
|
Sign up to set email alerts
|

Verbal memory impairment after left insular cortex infarction

Abstract: The findings suggest that the insula may be part of a functional network that mediates verbal memory. (J Neurol Neurosurg Psychiatry 1999;67:532-534)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 14 publications
(10 reference statements)
1
25
0
Order By: Relevance
“…Thus lesions to, or reductions in, insula volume may be associated with memory impairment. Such memory impairment has been described by Manes et al [45], who showed that individuals with left insula lesions had significantly poorer performances on verbal memory tasks than those with right insula lesions. Chen et al [46] conducted a study on victims of a fire disaster comparing 12 survivors with PTSD with 12 matched survivors without PTSD.…”
Section: Discussionmentioning
confidence: 83%
“…Thus lesions to, or reductions in, insula volume may be associated with memory impairment. Such memory impairment has been described by Manes et al [45], who showed that individuals with left insula lesions had significantly poorer performances on verbal memory tasks than those with right insula lesions. Chen et al [46] conducted a study on victims of a fire disaster comparing 12 survivors with PTSD with 12 matched survivors without PTSD.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the line bisection task was applied to report unilateral visual neglect. Right insular lesion patients showed grater severity of neglect over the somesthetic, visual, and auditory perception, when compared with left insular damage (see also Manes et al 1999c). In contrast, left-insular lesion patients presented small measures of neglect in the auditory modality.…”
Section: Neglectmentioning
confidence: 97%
“…Manes et al (1999c) compared verbal profiles between a group of four patients with right insular lesion and another with six patients with left insular lesions. Only patients who had performed within normal limits in measures of naming, word association, IQ, visual domain, and mental state were included in the study.…”
Section: Languagementioning
confidence: 99%
“…Thus, it is well positioned anatomically to play a crucial role in neural networks involved in verbal communication. Damage to the insula has been proposed as one of the possible neural substrates of conduction aphasia (Damasio & Damasio, 1980), apraxia of speech (Dronkers, 1996), auditory agnosia (Habib et al, 1995), dyslexia (Paulesu et al, 1996), and verbal memory (Manes, Springer, Jorge, & Robinson, 1999). Previous neuroimaging studies have implicated insular cortex in tasks involving articulation and speech coordination (Wise, Greene, Buchel, & Scott, 1999), short-term verbal memory (Paulesu et al, 1993), and music (Zatorre et al, 1994).…”
Section: Revising the Classic Model Of Language Localizationmentioning
confidence: 98%